Perceived Influence of Child Labour on Learning Performance of Junior Secondary School Students in Rivers State for Sustainable Educational Development in Nigeria - Ayodele Ebunolu Nwisagbo (Journal of Education for Sustainable Development Studies, 2024)
This study investigated the influence of child labour on the Learning performance of junior secondary school students for sustainable educational development Rivers State, Nigeria. A descriptive survey research design was used with a population of fourteen thousand, one hundred and sixty-seven students. The Taro Yamene formula yielded a sample size of 389. The researcher employed simple random sampling methods. The study was conducted with two research questions seeking answers to know how child labour influence junior secondary school attendance and how it influence the learning performance of these students in Obio-Akpor Local Government Area, Port Harcourt Rivers State, with two formulated hypotheses. The data was gathered using the “Influence of child labour on students’ learning performance Questionnaire”. Mean and standard deviation were used to answer the research questions, with the mean range determining the acceptability level as 2.50 to 3.49 and above, and the T-test statistic was used to test the hypotheses formulated at the 0.05 level of significance. It was discovered that Child labour demands that these students work long hours, leaving them with little or no time and energy to attend school, causing educational disruption with long-term effects on the child’s learning performance, Child labour was also discovered to cause physical and mental fatigue, which impairs the child’s ability to focus and concentrate on their academics. As a result, it was recommended that all children involved in child labour activities should have equal access to education while communities and individuals should be educated on the influence of child labour, Nigeria government should also eliminate poverty by creating employment opportunities for its population, which is seen as a leading cause of child labour, among others. This work will be a handy tool to educational administrators, counselors, parents, policy makers and other researchers.